Penegakan Hukum Bagi Pelaku Penyalahgunaan Narkotika Yang Dilakukan Oleh Anak Di Kota Banda Aceh - Zamharir; Mumtazinur (Jarima: Jurnal Ilmiah Mahasiswa Hukum Pidana Islam, 2025)
The problem of this study is how the criminal acts of drug abuse committed by children in the city of Banda Aceh. From the subject matter obtained several formula problems, i.e. 1) What form of crime is caused by the abuse of drugs perpetrated by children?, and 2) How the law enforcement of Polresta Kota Banda Aceh in counteracting the abuses of drugs by children. The type of research used in writing this article is empirical research with the research approach used is the Formal Yuridist Approach. As for the source of the data in this study, it's the police. Further, the data collection methods used are Interviews, Observations, and Documents or library materials. Then the data processing technique is carried out through several stages, namely: Data Identification, Data Reduction, Data Coding, and Data Editing. And the analysis used is qualitative analysis. The results of this study show that drug use among children from year to year continues to experience a significant increase. Internal factors include: (1) age; (2) misconceptions; and (3) lack of religious nature. External factors include (1) family; (2) economy; (3) environment; and (4) technological progress. The law enforcement is conducted in dealing with child drug abuse by conducting investigations, investigations and rehabilitation. In practice, the law enforcement carried out in Polresta Banda Aceh with all the obstacles experienced, has been in accordance with the SPPA Act but has not been done differently. The efforts of the law enforcement agencies to combat drug abuse are: 1) preventive efforts, such as socialization, conducting anti-drug campaigns, and routine anti-narcotics operations. 2) repressive efforts, including by giving decisive action to a child caught wetly abusing drugs.